Anterior choroidal artery ischaemic patterns predict outcome of carotid occlusion. Issue 6 (4th April 2012) - Lee, Meng; Saver, Jeffrey L; Hao, Qing; Starkman, Sidney; Salamon, Noriko; Ali, Latisha K; Kim, Doojin; Ovbiagele, Bruce; Song, Sarah; Raychev, Radoslav; Abcede, Hermelind; Fiaz, Rana; et al.
Abstract : Objective: To investigate whether anterior choroidal artery (AChA) territory sparing or AChA infarction restricted to the medial temporal lobe (MT), implying good collateral status, predicts good outcome, defined as modified Rankin Scale 0–2, at discharge in acute internal carotid artery (ICA) occlusion. Methods: The authors studied consecutive patients with acute ICA occlusion admitted to an academic medical centre between January 2002 and August 2010, who underwent MRI followed by conventional angiography. The pattern of AChA involvement on initial diffusion-weighted imaging was dichotomised as spared or MT only versus other partial or full. The association of AChA infarct patterns and good outcome at discharge was calculated by multivariate logistic regression with adjustment. Results: For the 60 patients meeting entry criteria, mean age was 68.3 years and median admission NIH Stroke Scale score was 19. AChA territory was spared or restricted to the MT in 27 patients and other partially involved or fully involved in 33 patients. AChA territory spared or ischaemia restricted to MT only, compared with other partial infarct patterns or full infarct, was independently associated with good discharge outcome (44.4% vs 12.1%, OR 7.24, 95% CI 1.32 to 39.89, p=0.023). Conclusion: In acute ICA occlusion, the absence of AChA infarction or restriction to the MT is an independent predictor of good discharge outcome. Analysis of AChA infarct patterns may improve early prognostication and decision-making.